Effect of temperature and time on alkaline pretreatment and alkaline microwave-assisted pretreatment on banana stem composition - Anggriani, Ulfa Meila; Novia, Novia; Melwita, Elda; Aprianti, Tine (CHEMICA: Jurnal Teknik Kimia, 2023)
Banana stem waste is a source of lignocellulose biomass with a high cellulose content and abundant availability in Indonesia. In this work, we investigated the effect of time and temperature on the decrease in rate of lignin in lignocellulose. Banana stem waste was pretreated with alkaline and alkaline microwave-assisted so that the percentage of lignin contained in lignocellulose biomass were reduced and the percentage of cellulose were increased. In alkaline pretreatment, 6% KOH is added to lignocellulose and heated to a hotplate during contact time variation (10, 20, 30, 40, and 50 min) with temperature variations (55, 65, 75, 85, and 95 oC). In pretreatment, an alkaline microwave–assisted 6% KOH solution was added to lignocellulose and heated for 20 min with temperature variations (55, 65, 75, 85, and 95 oC), then was put into a microwave that has a wave power of 360 Hz with variations in contact time (55, 65, 75, 85 and 95 min). After pretreatment, the sample was analyzed using the Chesson method to determine the percentage of cellulose, hemicellulose and lignin. Analysis showed that alkaline and microwave-assisted alkaline pretreatments effectively reduce the lignin percentage and increase the cellulose percentage in lignocellulose. The most remarkable performance in both pretreatments was obtained when working at 95 oC with a contact time of 50 min. Based on process optimization, it was concluded that microwave-assisted alkaline pretreatment reduced the percentage of lignin more and increased the percentage of cellulose compared to alkaline KOH pretreatment, which decreased the rate of lignin by 43.26% and increased the rate of cellulose by 60.68%. For further research, it can be continued to the next process, namely hydrolysis to produce glucose as a raw material for the bioethanol production process.